Hubungan Pengetahuan Orang Tua dengan Penatalaksanaan Demam pada Pasien Anak Balita - Sri Utari Mirahayu; Danur Jaya; Ahmad Rizal (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Fever is a common physiological response, particularly to infection, resulting from an increase in the hypothalamic temperature set point. Appropriate fever management in toddlers largely depends on parents’ knowledge, as inadequate understanding may lead to improper treatment and delayed medical care. This study aimed to determine the relationship between parental knowledge and fever management among toddlers at Grha Permata Ibu Hospital. A quantitative analytical study with a cross-sectional design was conducted. The study population consisted of 171 toddlers with fever who visited the outpatient clinic, emergency department, and inpatient ward during the previous three months. Using purposive sampling, 63 respondents were selected. Data were collected through structured questionnaires and analyzed using univariate and bivariate analyses with Spearman’s rank correlation test. The statistical analysis showed a significant relationship between parental knowledge and fever management (p = 0.001), indicating that parents with better knowledge tended to manage fever more appropriately. These findings highlight the importance of improving parental knowledge through health education to support proper fever management, reduce inappropriate home treatment, and encourage timely healthcare utilization. Strengthening educational interventions in healthcare settings may contribute to improving child health outcomes and preventing complications associated with improper fever management.